2018
DOI: 10.1111/jcmm.13932
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CASC9/miR‐519d/STAT3 positive feedback loop facilitate the glioma tumourigenesis

Abstract: Emerging evidence have illustrated the vital roles of long noncoding RNAs (lncRNAs) in glioma. Nevertheless, the majority of their roles and mechanisms in gliomagenesis are still largely unclear. In this study, we investigate the roles of lncRNA CASC9 on glioma tumourigenesis and authenticate its potential mechanisms. Results manifested that CASC9 was highly expressed in glioma specimens and cells, moreover, the ectopic overexpression was correlated with glioma patients’ clinic. Functional studies found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…Ectopic expression of CASC9 also occurs in gastric cancer, where CASC9 knockdown facilitates GC cell apoptosis [16]. In addition, the expression of CASC9 has been conformed higher in glioma tissues and cells, and CASC9 silencing hampered cell proliferative ability as well as invasion [30]. These findings demonstrated that regulating the expression of CASC9 may affect BC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of CASC9 also occurs in gastric cancer, where CASC9 knockdown facilitates GC cell apoptosis [16]. In addition, the expression of CASC9 has been conformed higher in glioma tissues and cells, and CASC9 silencing hampered cell proliferative ability as well as invasion [30]. These findings demonstrated that regulating the expression of CASC9 may affect BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that lncRNAs could serve as spongers for miRNAs [35]. Moreover, CASC9 has been certified to be capable of accelerating cancer development via sponging miRNAs, including ovarian cancer, glioma, and breast cancer [15, 30, 36]. Therefore, we explored whether CASC9 affected BC progression in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found the high expression of DLEU1 in GBM, the regulatory mechanism involved in DLEU1 up-regulation remained elusive. Existing evidences report that several key transcription factors contribute to the up-regulation of lncRNA in human cancers, such as SP1, ELK1, STAT3 and YY1 [30][31][32][33][34]. Using UCSC tool, SP1 was predicted as a transcription factor of DLEU1.…”
Section: The Transcription Factor Sp1 Contributed To the Up-regulatiomentioning
confidence: 99%
“…The prognostic factors for glioma consist of age, Karnofsky performance status (KPS) score, histologic grade, tumor necrosis, preoperative duration of symptoms, surgical resection extent and multimodal therapeutic strategies [3]. Glioma is characterized by diffusion and high invasiveness, but its potential mechanisms is still far from understanding [4]. Therefore, it is an urgent need to find new and effective strategies and establish potential therapeutic targets for the treatment of human glioma.…”
Section: Introductionmentioning
confidence: 99%